Effects of a viscosupplementation therapy on rabbit menisci in an anterior cruciate ligament transection model of osteoarthritis. (14th June 2017) - Levillain, A.; Magoariec, H.; Boulocher, C.; Decambron, A.; Viateau, V.; Hoc, T.
Abstract: The aim of this study was to evaluate the morphological, microstructural, and mechanical effects of a viscosupplementation therapy on rabbit menisci at an early stage of osteoarthritis (OA). Anterior cruciate ligament transection (ACLT) was performed in twelve male New-Zealand White rabbits on the right knee joint. Six of these twelve rabbits received a mono intra-articular injection of high molecular weight hyaluronic acid (HA) two weeks after ACLT. Six additional healthy rabbits served as controls. Medial menisci were removed from all right knees ( n  = 18) six weeks after ACLT and were graded macroscopically. Indentation-relaxation tests were performed in the anterior and posterior regions of the menisci. Collagen fiber organization and glycosaminoglycan (GAG) content were assessed by biphotonic confocal microscopy and histology, respectively. Viscosupplementation significantly ( p  = 0.002) improved the surface integrity of the medial menisci compared to the operated non-treated group. Moreover, the injection seems to have an effect on the GAG distribution in the anterior region of the menisci. However, the viscoelastic properties of both operated groups were similar and significantly lower than those of the healthy group, which was explained by their modified collagen fiber organization. They displayed disruption of the tie fibers due to structural alterations of the superficial layers from which they emanate, leading to modifications in the deep zone. To conclude, the viscosupplementation therapy prevents macroscopic lesions of the menisci, but it fails to restore their collagen fiber organization and their viscoelastic properties. This finding supports the role of this treatment in improving the lubrication over the knee.